STUDIES ON THE FARM MACHINERY MANAGEMENT - Mariana DUMITRU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper presents studies and researches made on machines performance, which is one of the most important component of the economic performance of a farm. We made measurements for determination of work quality and energetic index for tractors, considering that tractors are the main energetic power used in modern agriculture anywhere, that is why the improving of the quality and energetic index of tractors and machines is very important. The aim of the research is to improve power performances and to increase the efficiency of tractors and agricultural machines. The productivity is one of the most significant characteristics of tractors and agricultural machines, especially of harvesting machines, which are the most important machines for harvesting cereals. We wanted to emphasize that designing and making these complex agricultural machines has much evolved in the last years, from the productivity point of view and from the design and interior comfort as well.